Cancer-Type Organic Anion Transporting Polypeptide 1B3 Is Localized in Lysosomes and Mediates Resistance against Kinase Inhibitors - Haberkorn, Bastian; Oswald, Stefan; Kehl, Niklas; Geßner, Arne; Taudte, Verena; Dobert, Jan; Zunke, Friederike; Fromm, Martin; König, Jörg (Molecular Pharmacology, 2022)
Cancer-type organic anion transporting polypeptide 1B3 (CtOATP1B3), a splice variant of the hepatic uptake transporter OATP1B3 (liver-type), is expressed in several tumor entities, including colorectal carcinoma (CRC) and breast cancer. In CRC, high OATP1B3 expression has been associated with reduced progression-free and overall survival. Several kinase inhibitors used for antitumor treatment are substrates and/or inhibitors of OATP1B3 (e.g., encorafenib, vemurafenib). The functional importance of CtOATP1B3 has not been elucidated so far. Human embryonic kidney 293 cells stably overexpressing Ct-OATP1B3 protein were established and compared with control cells. Confocal laser scanning microscopy, immunoblot, and proteomics-based expression analysis demonstrated that Ct-OATP1B3 protein is intracellularly localized in lysosomes of stably transfected cells. Cytotoxicity experiments showed that cells recombinantly expressing the Ct-OATP1B3 protein were more resistant against the kinase inhibitor encorafenib compared with control cells [e.g., encorafenib (100 mM) survival rates: 89.5% versus 52.8%]. In line with these findings, colorectal cancer DLD1 cells endogenously expressing Ct-OATP1B3 protein had poorer survival rates when the OATP1B3 substrate bromosulfophthalein (BSP) was coincubated with encorafenib or vemurafenib compared with the incubation with the kinase inhibitor alone. This indicates a competitive inhibition of Ct-OATP1B3–mediated uptake into lysosomes by BSP. Accordingly, mass spectrometry-based drug analysis of lysosomes showed a reduced lysosomal accumulation of encorafenib in DLD1 cells additionally exposed to BSP. These results demonstrate that Ct-OATP1B3 protein is localized in the lysosomal membrane and can mediate transport of certain kinase inhibitors into lysosomes, revealing a new mechanism of resistance.
Created from Fastlane, Scopus look-up